Safety, Pharmacokinetics and Pharmacodynamics of Selgantolimod, an Oral Toll-Like Receptor 8 Agonist: A Phase Ia Study in Healthy Subjects. Issue 3 (April 2020) - Reyes, Maribel; Lutz, Justin D; Lau, Audrey H; Gaggar, Anuj; Grant, Ethan P; Joshi, Adarsh; Mackman, Richard L; Ling, John; Tan, Susanna K; Ayithan, Natarajan; Daffis, Stephane; Woo, Jacky; et al.
Background: Selgantolimod is a novel oral, selective Toll-like receptor 8 (TLR8) agonist in development for the treatment of chronic hepatitis B (CHB). TLR8 is an endosomal innate immune receptor and a target for treatment of viral infections. This first-in-human study investigated the safety, tolerability, pharmacokinetics (PK) and pharmacodynamics (PD) of selgantolimod in healthy volunteers. Methods: Of 71 subjects enrolled, 59 received a single dose of selgantolimod (0.5, 1.5, 3 or 5 mg) or placebo, and 12 were evaluated for food effect. Safety, PK and PD activity by induction of cytokines, chemokines and acute phase proteins were assessed. PK/PD analyses were conducted. Results: Single doses of 0.5–5 mg were generally safe. No serious adverse events (AEs) or AEs leading to discontinuation were reported, and most were Grade 1 in severity. Selgantolimod displayed rapid absorption and dose-proportional PK and PD activity. Food had minimal effect on PK but resulted in diminished PD activity. In PK/PD analyses, near-saturation of induction for most evaluated biomarkers occurred at the 5-mg dose. Conclusions: Single doses of up to 5 mg selgantolimod were safe and induced dose-dependent PD responses. These data support evaluation of selgantolimod in combination with other agents in future clinical studies of CHB. Australian New Zealand Clinical Trials Registration: ACTRN12616001646437.